B173 Local anesthetics affect tumor biology in an ex vivo tissue model of non-small cell lung cancer. (11th August 2022) - Krömer, J; Hoang, NA; Sittig, D; Welling, C; Junk, D; Mölleken, J; Zönnchen, J; Monecke, A; Krämer, S; Kallendrusch, S; Piegeler, T
Abstract : Background and Aims: Rates of tumor-related death in lung cancer are still high, despite improved treatment options and a deeper understanding of tumor biology and immune responses. Perioperative use of local anesthetics might influence outcome after tumor surgery(1), an effect possibly based on anti-inflammatory properties, leading to an inhibition of signaling processes crucial for metastasis(2–4). However, effects of local anesthetics on tumor biology in "real-life" tumors has not been investigated yet. Methods: After surgical removal, tumor slices from patients with NSCLC were cultured ex vivo and treated with different concentrations (1µM/10µM) of ropivacaine or lidocaine in absence or presence of cisplatin (3µM, n=9). After 72 h tissues were analyzed using immune-histochemistry/-fluorescence and Western blot. Levels of Ki67 (proliferation), cPARP (apoptosis), intercellular-adhesion-molecule-1 (ICAM-1), and CD163 expression (in tumor-associated macrophages) were assessed. The study was approved by the ethics committee at the University of Leipzig (protocol number 370/13-ek) and funded by the ESRA Research Grant. Results: Ropivacaine reduced the proliferating tumor cell fraction by 20% (1µM) and 27% (10µM), respectively. Both ropivacaine and lidocaine increased the share of apoptotic tumor cells in a dose-dependent manner. Expression patterns of ICAM-1 as well as of tumor associated macrophages (CD163) were altered by lidocaine and ropivacaine in immunofluorescence staining. Conclusions: Local anesthetics might alter tumor-cell biology and the tumor-microenvironment ex vivo . Proliferation and ICAM-1 expression of tumor cells, along with CD163 expression of macrophages were affectedby local anesthetics, thus supporting aless invasive and less malignant tumor phenotype. This once more underlines the possible impact of these drugs on patient outcome after tumor surgery.